Screening and Biochemical Characterization of Wheat Cultivars Resistance to Magnaporthe oryzae pv Triticum (MoT) - Biswas, Chandra Shekhar; Hannan, Afsana; Monsur, Abul; Sagor, G H M (Journal of Plant Stress Physiology, 2020)
Global food security is seriously threatened due to increased frequency and occurrence of fungal diseases. One example is wheat blast caused by Magnaporthe oryzae is a fungal diseases of rice, wheat, and other grasses, that can destroy the whole food production to sustain millions of people. Wheat blast was first detected in february 2016 with a serious outbreak in Asia. Assessment of the available germplasms to stress tolerant/resistant is one of the best options for developing stress tolerant crop varieties. In this study, a total of sixteen wheat cultivars were collected and test their disease severity to blast pathogen Magnaporthe oryzae pv. Triticum (MoT). Among the varieties, BARI Gom 33 exhibited partially resistance against blast pathogen, whereas all other genotypes become susceptible to MoT. Different yield and yield contributing characters of both resistant and susceptible cultivars were also evaluated and found no significant differences among them. To understand the underlying mechanism of resistance in BARI Gom 33, antioxidant enzyme activity, concentration of reactive oxygen species and cellular damage after fungal infection were also evaluated and found that activities of ascorbate peroxidase (APX), catalase (CAT) and peroxidase (POD) were higher in BARI Gom 33 than BARI Gom 25 and BARI Gom 31. The hydrogen peroxide (H2O2) and malondealdehyde (MDA) content in BARI Gom 33 was low compare to BARI Gom 25 and BARI Gom 31, which may due to greater increase of the APX, CAT and POD in resistant genotypes. Thus, it may suggest that a more efficient antioxidative defense system in BARI Gom 33 during the infection process of M. oryzae restricts the cell damage caused by the fungus. The identified genotypes can either be used directly in the blast prone area or as a source of resistance to further development of blast resistance high yielding wheat variety.